2014
DOI: 10.1093/nsr/nwu028
|View full text |Cite
|
Sign up to set email alerts
|

Novel applications of statins for bone regeneration

Abstract: The use of statins for bone regeneration is a promising and growing area of research. Statins, originally developed to treat high cholesterol, are inhibitors of the enzyme 3-hydroxy-3-methylglutaryl, the rate-limiting enzyme of the mevalonate pathway. Because the mevalonate pathway is responsible for the synthesis of a wide variety of important biochemical molecules, including cholesterol and other isoprenoids, the effects of statins are pleiotropic. In particular, statins can greatly affect the process of bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 133 publications
0
70
0
3
Order By: Relevance
“…In particular, statins are shown to be effective against A. actinomycetemcomitans and Porphyromonas gingivalis , 2 of the major species of bacteria implicated in periodontitis pathogenesis. Furthermore, statins are shown to inhibit tissue‐degrading enzymes (i.e., matrix metalloproteinases) and to exert a pro‐proliferative effect on mesenchymal stromal cells and endothelial progenitor cells . Statins are also shown to enhance osteoblastic differentiation and viability, bone morphogenetic protein and vascular endothelial growth factor expression and to interfere with bone resorption and osteoclastogenesis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, statins are shown to be effective against A. actinomycetemcomitans and Porphyromonas gingivalis , 2 of the major species of bacteria implicated in periodontitis pathogenesis. Furthermore, statins are shown to inhibit tissue‐degrading enzymes (i.e., matrix metalloproteinases) and to exert a pro‐proliferative effect on mesenchymal stromal cells and endothelial progenitor cells . Statins are also shown to enhance osteoblastic differentiation and viability, bone morphogenetic protein and vascular endothelial growth factor expression and to interfere with bone resorption and osteoclastogenesis …”
Section: Discussionmentioning
confidence: 99%
“…Statins present high efficacy and tolerability in general, are rather inexpensive and by inhibiting cholesterol synthesis reduce the risk for cardiovascular diseases . Besides reducing cholesterol levels, statins have also been shown to possess antimicrobial, antiviral, fungicidal, anti‐inflammatory and pro‐osteogenic properties and to enhance the number and/or function of mesenchymal stromal cells and/or endothelial progenitor cells; thus, statins appear relevant in periodontology, either in preventing disease or in periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the benefits of statins, especially SIM, on bone formation as well as on the inhibition of bone resorption (Horiuchi & Maeda, ; Moshiri, Sharifi, & Oryan, ; Mundy, ; Shah, Werlang, Kasper, & Mikos, ; Zhang et al, ). Within the family of statins, PITA presents some interesting properties, in particular its lower price, hydrophilic properties and its comparable efficiency compared to other statins (i.e., SIM) at much lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical cues may promote healing by influencing the inflammatory pathway (such as statins 25 ) or by directly acting on cells (such as site-specific bisphosphonate therapy 26 ). Locally delivered small molecules for bone tissue engineering is a growing area of interest in the regenerative medicine community 27 .…”
Section: Signalsmentioning
confidence: 99%